Effect of Soot Particulate Exposure on Placental Malondialdehyde Levels, Placental Weight and Pregnancy Outcomes in Rats (Ratus novergicus) - Lestari Sudaryanti (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2026)
Particulate Soot, a product of incomplete combustion processes from industry, fuel emissions and other combustion products, is a component of air pollutants known to be hazardous to health because it is cytotoxic. Adverse health effects depend on the length of exposure and levels in the air, through oxidative stress mechanisms its toxicity affects all body systems including the reproductive system. The placenta, which plays an important role in the growth and development of the fetus, is known to be susceptible to damage in oxidative stress events, affecting pregnancy outcomes. Malondialdehyde (MDA), a biomarker of lipid peroxidation, is often used to assess the level of oxidative stress. However, the effects of soot particulate exposure on placental MDA levels and pregnancy outcomes remain poorly understood. This study aimed to investigate the impact of soot particulate exposure on placental MDA levels, and its effect on placental weight and pregnancy outcome of rats (Rattus norvegicus). Pregnant rats were divided into a control group and 4 experimental groups. The experimental groups were exposed to soot particulates at concentrations of 532 mg/m³ and 1064 mg/m³ for 4 and 8 hours per day throughout gestation, while the control group was exposed to clean air in the chamber. Placental tissues were collected at the end of pregnancy, weighed and examined for MDA levels using the thiobarbituric acid reactive substances (TBARS) assay. Pregnancy outcomes such as fetus weight, fetus length, number of live fetuses and number of intra-uterine deaths were measured and recorded, then statistically analysed. Placental MDA levels in all exposure groups increased significantly compared to the control group (p < 0.05), indicating oxidative stress. Observations in the exposed groups showed a decrease in placental weight, fetal weight, fetal length, number of live fetuses and increased intrauterine death compared to the control group significantly (p < 0.05). Placental MDA levels had a significant effect on placental weight, and pregnancy outcome, the greater the dose and duration of exposure the worse the pregnancy outcome of rats. These findings suggest that exposure to particulate soot causes oxidative stress in placental tissues, resulting in poor pregnancy outcomes. Revealing the potential risks of particulate pollution on reproductive health and foetal development, further research is needed on the mechanism of exposure to find the best solution.